Immune checkpoint inhibitor-related myocarditis during DUO-E regimen for endometrial cancer: The first case report in gynecologic oncology - Eri Yamabe; Hironori Yamamoto; Keita Asano; Taku Yasui; Masashi Fujita; Tsuyoshi Hisa; Miho Kitai (Gynecologic Oncology Reports)
Background: Immune checkpoint inhibitors (ICIs) are increasingly used in gynecologic oncology, with the DUO-E regimen—carboplatin, paclitaxel, and durvalumab—recently approved in Japan for advanced or recurrent endometrial cancer. However, ICI-related myocarditis (ICI-M) is a rare but potentially fatal adverse event requiring prompt recognition and treatment. Case Presentation: A 74-year-old woman with advanced endometrial cancer developed ICI-M following four cycles of DUO-E therapy. Sixteen days post-treatment, she presented with fever and fatigue. Markedly elevated troponin I (39.8 ng/mL), new-onset complete right bundle branch block, and a reduced left ventricular ejection fraction (40 %) raised suspicion for ICI-M. Endomyocardial biopsy revealed diffuse CD8 + T-cell infiltration and myocyte necrosis, consistent with active myocarditis. High-dose methylprednisolone (1 g/day) was promptly initiated, resulting in rapid cardiac recovery and clinical stabilization. Chemotherapy was successfully resumed after steroid tapering. Conclusion: This is the first reported case of ICI-M during DUO-E therapy for endometrial cancer. It underscores the importance of early clinical suspicion, rapid multidisciplinary collaboration, and timely intervention in managing ICI-M, particularly in high-risk patients. Continuous vigilance is warranted throughout the course of ICI therapy.